THE DEMAND ELASTICIY OF UNDERGRADUATE STUDENTS FOR BEEF INS SANTA MARIA, RS - Guerra, Renata Rojas; Kirinus, Jackeline Karsten; Dörr, Andréa Cristina; Nörnberg, José Laerte (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708814 The beef is a food of great relevance in the Brazilian diet. In this sense, the objective of this study was to consider the influence of students in determining the consumption of beef in Santa Maria, Rio Grande do Sul, Brazil, and to estimate income and price elasticities for the demand for this product through the model regression of log-linear plus a dummy variable. To this end, we collected primary data through forms applied to students of Federal University of Santa Maria, Brazil (UFSM) distributed in supermarkets and consumers around the city. Data collection occurred from March to April 2011. The results confirmed the existence of differences between the consumption behavior of both strata. The growth rate of the amount of beef consumed by the inhabitants of Santa Maria is 37.9% lower for students than for the rest of the population. For other variables, confirmed the existence of a significant relationship between these, so their coefficients of elasticity were about -0.33% to 0.087% and prices for the income elasticity. It can be concluded that the population of the municipality of Santa Maria, RS comprises a significant portion of students and they often have a different consumption pattern, which can influence the behavior of the demand curve for food in the city.